La judicialización de los derechos reproductivos en perspectiva comparada: el Anticonceptivo Oral de Emergencia en Perú (2006-2009) y Chile (2007-2008) - Silva Andujar, Nicolás (2024)
This study examines the judicialization of reproductive rights in Peru and Chile, focusing on the influence of extralegal factors on judicial decisions related to the distribution of the Emergency Oral Contraceptive (EOC) during the periods 2006-2009 and 2007-2008, respectively. Through a comparative analysis, the study explores the impact of ideology, legal culture, and conservative social movements on judicial decision-making in both cases. The study concludes that these determinants, acting interdependently, function as causal mechanisms in judicial decision-making, explaining shifts in positions and arguments in both Chile and Peru. Additionally, the study highlights that the judicialization of emergency contraceptive methods has had both positive and negative impacts on women’s reproductive rights.